Decentralising: The implementation of regionalisation and co-management under the post-2013 Common Fisheries Policy. (December 2015) - Eliasen, Søren Q.; Hegland, Troels J.; Raakjær, Jesper
Abstract: This article reviews early experiences with what is commonly referred to as 'regionalisation'. Initially, the article briefly recalls the shortcomings of the traditional, highly centralised governance structure of the Common Fisheries Policy of the European Union, for which regionalisation was widely perceived as a solution, while at the same time providing an overview of the policy processes and various inputs that led to the provisions of recent regulation. Subsequently, the article presents empirical experiences related to the actual implementation and performance of the regional structures in the North and Baltic Seas and discusses the extent to which the adopted model of regionalisation is appropriate in light of the objectives it was intended to advance. Finally, the article offers some scenarios of possible 'futures' of the regional structures. Highlights: The modus operandi of regionalisation falls short in active stakeholder involvement. The High Level Groups in the regions appear to operate as elitist 'mini-councils'. Regionalisation requires political will and dedicated efforts for change. Article 18 marks the beginning and not the end of political support for regionalisation. Article 18 has the flexibility to accommodate a move towards genuine regionalisation.